SM 05-0900 The connection between unintentional injury and human rights. (November 2018) - Ryan, Mark
Abstract : The financial and human costs of unintentional injury, particularly to children, are cause for global concern. Many local, national and international agencies have thus incorporated unintentional injury prevention into their top strategic priorities. Yet, it can be argued that unintentional injury is not commonly associated with an important area of international normative structure: human rights. This study primarily aims to display how deeply unintentional injury is already anchored into core human rights areas. Secondarily, this study highlights gaps between unintentional injury and human rights and provides a map for how the injury prevention community can fill these gaps while harnessing existing injury-based rights. A content analysis of fourteen international and regional human rights texts was conducted to determine if they provide any protections from unintentional injury. A clause was identified as explicitly protecting from unintentional injury if it met two conditions: 1) the content of the clause included any form of the words 'injury', 'safety', 'accident' or 'hazard', and 2) these words referred to physical injury that is not intentionally inflicted. 19 explicit protections were found in the analyzed texts; 12 pertain to workplace injuries. Populations with specific protections include children, individuals with disabilities, women and migrant workers. There were no references to specific injury mechanisms. A number of populations vulnerable to injury, such as older persons, were not referenced. This analysis reveals a clear relationship between unintentional injury and human rights. Injury prevention professionals can utilize these protections in myriad ways. There is a possibility for the injury prevention community to advocate for additional protections around high-priority injury mechanisms and additional vulnerable populations. There is also an opportunity to conduct research to better understand how unintentional injury already intersects with other manifestations of human rights such as social norms, policy, philosophy, and written language.